Varied Differences in the Health Status Between Medicare Advantage and Fee-for-Service Enrollees - Yunjie Song PhD (Inquiry: The Journal of Health Care Organization, Provision, and Financing, 2014)
This article examines the differences in mortality measured health status between the Medicare Advantage (MA) program and Fee-for-Service (FFS) program from 1999 to 2007. At the national level, differences in mortality rates were associated with MA market share. In some counties, enrollees in the MA program were 40% less likely to die than their peers in the FFS program, but in other counties, they were 20% more likely to die. Cost shifting between the two programs could bias county classifications of average FFS spending, and enlarged disparities in health status could make it difficult to evaluate risk adjusters.